2009
DOI: 10.1111/j.1582-4934.2008.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of thyrotropin receptor in hepatocytes: not a case of illegitimate transcription

Abstract: The function of thyrotropin (TSH) in the thyroid gland is mediated by thyrotropin receptor (TSHR). In addition to the thyroid, TSHR expression has been described in some non-thyroidal tissues, although it is uncertain whether TSHR is present in hepatocytes. One study has reported hepatic expression of TSHR mRNA, but this was considered to be because of illegitimate transcription, and there has not been a study investigating its protein expression and function in hepatocytes. Here, we examined the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 31 publications
3
63
0
2
Order By: Relevance
“…10 In the present study, by showing its coupling to the intracellular cAMP system and the expression of HMGCR, we established the functionality of this receptor in liver cells. This was unequivocally proven by the abolishment of the effects of TSH in cells treated with specific TSHR monoclonal antibodies or lentiviral TSHR siRNA to silence the expression of TSHR.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…10 In the present study, by showing its coupling to the intracellular cAMP system and the expression of HMGCR, we established the functionality of this receptor in liver cells. This was unequivocally proven by the abolishment of the effects of TSH in cells treated with specific TSHR monoclonal antibodies or lentiviral TSHR siRNA to silence the expression of TSHR.…”
Section: Discussionmentioning
confidence: 82%
“…We previously demonstrated that TSHR expressed in liver cells, including human liver cells. 10 Here, we took further steps to examine and demonstrate a functional coupling of the TSHR to the cAMP system in the cells. Treatment with TSH significantly stimulated cAMP production in liver cells over the control ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported mechanisms for the development of hypercholesterolemia and an increase in low density lipoproteins in hypothyroidism include decreased fractional clearance of LDL by a reduced number and reduced activity of LDL receptors in the liver (4,13) . In vivo and in vitro studies of Wei Zhang et al (16) showed the presence of TSH receptor on liver cells. TSH itself upregulates the expression of HMG-COA -reductase by acting on a TSH receptor in hepatocyte membrane and therefore promotes cholesterol synthesis in liver (17) .…”
Section: Sample (Blood) Collectionmentioning
confidence: 99%
“…Recently, multiple studies have found that extrathyroidic tissues express TSHR [11]. Our previous studies [12,13] demonstrated that functional TSHR was expressed samples were collected. The liver, heart and kidney were weighed, and the liver was divided into three parts.…”
mentioning
confidence: 99%